2013
DOI: 10.1021/ja400755e
|View full text |Cite
|
Sign up to set email alerts
|

Migration Insertion Polymerization (MIP) of Cyclopentadienyldicarbonyldiphenylphosphinopropyliron (FpP): A New Concept for Main Chain Metal-Containing Polymers (MCPs)

Abstract: We report a conceptually new polymerization technique termed migration insertion polymerization (MIP) for main chain metal-containing polymer (MCP) synthesis. Cyclopentadienyldicarbonyldiphenylphosphinopropyliron (FpP) is synthesized and polymerized via MIP, resulting in air stable poly(cyclopentadienylcarbonyldiphenylphosphinobutanoyliron) (PFpP) displaying narrow molecular weight distribution. The backbone of PFpP contains asymmetric iron units connected by both phosphine coordination and Fe-acyl bonds, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
99
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 37 publications
3
99
0
Order By: Relevance
“…Furthermore, the metal-acyl unit has been introduced into the main chain of polymers to form potential functional organometallic materials [10,11], which develops the new application fields of metal-acyl complexes. In addition, since the successful elucidation of the structure of [Fe]-hydrogenase [12] indicated that an acyl-iron ligates to the active site of [Fe]-hydrogenase [13e15], many acyl iron complexes have been synthesized as biomimetic models for the active site of [Fe]-hydrogenase [16e25], which greatly promotes the development of metal-acyl complexes and widely broadens the potential application areas of metal-acyl complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the metal-acyl unit has been introduced into the main chain of polymers to form potential functional organometallic materials [10,11], which develops the new application fields of metal-acyl complexes. In addition, since the successful elucidation of the structure of [Fe]-hydrogenase [12] indicated that an acyl-iron ligates to the active site of [Fe]-hydrogenase [13e15], many acyl iron complexes have been synthesized as biomimetic models for the active site of [Fe]-hydrogenase [16e25], which greatly promotes the development of metal-acyl complexes and widely broadens the potential application areas of metal-acyl complexes.…”
Section: Introductionmentioning
confidence: 99%
“…11 Unfortunately, the monomers cannot be isolated, and the resulting polymer cross-links over time, rendering it difficult to investigate the polymerization in detail. 29 FpC3P contains a functional group of CpFe(CO) 2 (Fp) with a phosphine ligand tethered via a propyl spacer. 29 FpC3P contains a functional group of CpFe(CO) 2 (Fp) with a phosphine ligand tethered via a propyl spacer.…”
Section: Introductionmentioning
confidence: 99%
“…FpC3P can undergo a migration insertion reaction (MIR) at elevated temperature (>40°C). 29 Consequently, intermolecular MIRs are promoted, leading to a new type of main chain MCP, PFpC3P. phosphine).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations